"Filthy Lapdogs, " "Jerks, " and "Hitler": Making Sense of Insults in International Relations. Issue 3 (7th August 2020) - Rousseau, Elise; Baele, Stephane J
Abstract: This paper offers an original theoretical framework for the study of insults in international relations (IR). Bringing into IR the two main theoretical approaches to aggravating language, slurs and dysphemisms, we conceptualize insults' disruptive impact on international interactions in a way that explains their logic, consequences, and risks. Specifically, we argue that insults constitute both at once tactical tools used by international actors to achieve their interests by disrupting an interaction and modifying the payoffs associated with it and linguistic artifacts constructing and sharpening self- and other identities. The components of our theoretical framework are illustrated with a wide range of empirical cases of international insults.